Evolution and Comparative Physiology of Luqin-Type Neuropeptide Signaling - Yañez-Guerra, Luis Alfonso; Elphick, Maurice R. (Frontiers in Neuroscience, 2020)
Luqin is a neuropeptide that was discovered and named on account of its expression in Left Upper Quadrant cells of the abdominal ganglion in the mollusc Aplysia californica. Subsequently, luqin-type peptides were identified as cardio-excitatory neuropeptides in other molluscs and a cognate receptor was discovered in the pond snail Lymnaea stagnalis. Phylogenetic analyses have revealed that orthologs of molluscan luqin-type neuropeptides occur in other phyla; these include neuropeptides in ecdysozoans (arthropods, nematodes) that have a C-terminal RYamide motif (RYamides) and neuropeptides in ambulacrarians (echinoderms, hemichordates) that have a C-terminal RWamide motif (RWamides). Furthermore, precursors of luqin-type neuropeptides typically have a conserved C-terminal motif containing two cysteine residues, although the functional significance of this is unknown. Consistent with the orthology of the neuropeptides and their precursors, phylogenetic and pharmacological studies have revealed that orthologous G-protein coupled receptors mediate effects of luqin-type neuropeptides in spiralians, ecdysozoans and ambulacrarians. Luqin-type signalling originated in a common ancestor of the Bilateria as a paralog of tachykinin-type signalling but, unlike tachykinin-type signalling, luqin-type signalling was lost in chordates. This may largely explain why luqin-type signalling has received less attention than many other neuropeptide signalling systems. However, insights into the physiological actions of luqin-type neuropeptides (RYamides) in ecdysozoans have been reported recently, with roles in regulation of feeding and diuresis revealed in insects and roles in regulation of feeding, egg laying, locomotion and lifespan revealed in the nematode Caenorhabditis elegans. Furthermore, characterisation of a luqin-type neuropeptide in the starfish Asterias rubens (phylum Echinodermata) has provided the first insights into the physiological roles of luqin-type signalling in a deuterostome. In conclusion, although luqin was discovered in Aplysia over thirty years ago, there is still much to be learnt about luqin-type neuropeptide signalling. This will be facilitated in the post-genomic era by the emerging opportunities for experimental studies on a variety of invertebrate taxa.